A GPS TEC-based Ionospheric-M Index over Malaysia - Sadia, Mostofa; Mardina, Abdullah; Mohamad Tariqul, Islam; Siti Aminah, Bahari; Ahmmed, Mohammad Badal (Institute of Electrical and Electronics Engineers Inc., 2022)
Space weather can have a profound impact on trans-ionospheric radio signals. Through quantifying the intensity of a space weather event, from its genesis at the Sun to its effect on the ionosphere, many physical parameters must be extracted from scientific data. Consequently, they are used for the quick conveyance of a streamlined but sufficient space situational awareness. Nevertheless, space weather-driven ionospheric phenomena can impact many consumers in the communication and navigation domains, which are not adequately served by the existing indices. Here we propose and discuss the advantage of the new ionospheric index, known as M index over the Malaysian region in terms of disturbed storm time (Dst) and Total Electron Content (TEC). We took a geomagnetic storm event on 1st and 2nd June 2013. It has been found that the storm started effects over this region with a time delay of approximately 21 hours. The suggested ionospheric disturbance index may overcome several shortcomings of previous ionospheric measurements and may be appropriate as a possible driver for an ionospheric space weather scale.